2010
DOI: 10.1186/1465-9921-11-82
|View full text |Cite
|
Sign up to set email alerts
|

Combined forced oscillation and forced expiration measurements in mice for the assessment of airway hyperresponsiveness

Abstract: BackgroundPulmonary function has been reported in mice using negative pressure-driven forced expiratory manoeuvres (NPFE) and the forced oscillation technique (FOT). However, both techniques have always been studied using separate cohorts of animals or systems. The objective of this study was to obtain NPFE and FOT measurements at baseline and following bronchoconstriction from a single cohort of mice using a combined system in order to assess both techniques through a refined approach.MethodsGroups of allerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 19 publications
1
74
0
3
Order By: Relevance
“…In addition to FOT, the flexiVent system can also be used to collect other types of lung function [8][9][10] or cardiovascular Table 4. System Comparison.…”
Section: Representative Resultsmentioning
confidence: 99%
“…In addition to FOT, the flexiVent system can also be used to collect other types of lung function [8][9][10] or cardiovascular Table 4. System Comparison.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Using a constant phase model to assess respiratory system mechanics, the present study showed that OD caused dose-dependent AHR in Rn, G, and H. These data demonstrate that OD exposure affects the responses to MCh in proximal parts of the lung represented by Rn, providing information about large airway responses. Distal lung compartments, represented by G, a reflection of large and small airway narrowing, and H, which represents altered dynamic lung elastance and increases due to derecruitment of lung tissue from airway closure (40,41), were also increased by OD treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Pulmonary function tests were performed on a FlexiVent system (Scireq) as previously described (Hashimoto et al, 2016; Shalaby, Gold, Schuessler, Martin, & Robichaud, 2010). The mice were euthanized by an intraperitoneal injection of pentobarbital sodium (100 mg/kg of body weight) and connected to the FlexiVent system after tracheotomy.…”
Section: Methodsmentioning
confidence: 99%